Multidisciplinary Support for Pregnant and Parturient with Congenital Heart Disease - S. O. Siromakha; Y. V. Davydova; A. Yu. Limanska; V. V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2019)
Adults with corrected or uncorrected congenital heart defects form a separate cohort of patients – GUCH (grown-up with congenital heart). GUCH patients usually have a certain degree of heart failure, arrhythmias, an increased risk of infective endocarditis; some of them require additional heart surgery, with an increased risk of developing sudden cardiac death syndrome. Experts from the European Society of Cardiologists are considering questions and medical support for pregnancy, childbirth and postpartum period in women from a GUCH cohort. In accordance with the ESC recommendations, a multi-disciplinary team consisting of specialists from M. Amosov National Institute for Cardiovascular Surgery and the Institute of Paediatrics, Obstetrics and Gynaecology, NAMS of Ukraine, was created in Ukraine in 2013.Objectives. Reducing maternal and infant mortality and disability, as well as providing optimal management and delivery strategy for pregnant women with congenital cardiac pathology.Materials and methods. Counselling assistance was provided to 2 815 pregnant women with cardiac pathology, 116 women underwent inpatient treatment since 2013. The group of GUCH patients consisted of 64 women, 61 of them were pregnant, 3 were parturient. 52 patients had structural CHD, 12 women suffered from congenital anomalies of the cardiac conduction system. There were patients with a corrected CHD and satisfactory result (n=4), with CHD after palliation or significant residual components of the defect (n=13), and GUCH pregnant with uncorrected CHD (n=35). Some inpatient women received non-surgical treatment (n=11, 17%). In 53 women (50 pregnant and 3 parturient), who underwent any type of surgery, 42 cardiac and vascular interventions, 18 caesarean sections were performed. Cardiac surgeries included endovascular interventions (n=22), operations with CPB (n=19), one closed intervention on the femoral artery. There were 23 elective operations, and 19 urgent or emergency cases.Results. One maternal and two foetal losses were observed in a group of pregnant women (parturient) who underwent emergency intervention with CPB. There was no more maternal loss or foetal loss in all other cases (n=47), pregnancies ended either on a term delivery or on a Caesarean section without complications with high functional indicators in new-borns by the Apgar scale. The current level of cross-sectoral specialized care for GUCH -pregnant with special needs greatly reduces the risk of mortality and disability in the mother and child.Conclusions. The first line of defence of GUCH-women of childbearing age involves primary prevention of major cardiac events, namely preconceptional counselling at specialized expert centres, and their preconceptional preparation, multidisciplinary support of such women throughout pregnancy, delivery and postpartum period.